Representations of child abuse in contemporary French teenage fiction - Rutherford-Chapman, Claire (2016)
Child abuse began to emerge as a central topic depicted in Western children’s and teenage realist fiction from around the 1990s, peaking in prevalence around the turn of the century and into the early years of the twenty-first century. In this thesis I explore the formal expression of abuse and trauma in a corpus of twenty French texts published between 1992 and 2008 for young-adolescent readers aged between 10 and 16 years. The project begins with a Propp-inspired structural model of child-abuse plot features and characters, which identifies a set cast of protagonists across the corpus which serve a specific functional role in the narrative. I then focus on the three main narratological categories of voice, mood and time, using Genette’s Discours du récit as a framework for a close reading of the abuse texts, whilst also drawing upon various trauma theorists, to explore how choice of narrator, focalizing character and temporal perspectives are manipulated to express different aspects of and perspectives on abuse and the psychological impact of abuse in particular. The final chapter is an analysis of the means used by both protagonists within the texts, and the authors of the texts, to communicate and express abuse and trauma on a personal level, to other characters, and to readers. By drawing upon structural and narratological studies as well as trauma theory in my analysis, I show that form and content are inextricably linked across the corpus. Indeed, the protagonists’ traumatic memories and painful experiences are expressed both on a diegetic level via the characters, and also reflected in the formal and structural features of the texts.